Study on the Potential Rare Earth Elements in Coal Combustion Product from Banjarsari Power Plant, South Sumatera. Issue 1 (May 2021) - Firman,; Haya, A
Abstract: Coal combustion produt (CCP) from Banjarsari power plant, both fly ash and bottom ash are numerous and have not been utilized optimally. CCP contains rare earth elements so that the potential needs to be assessed as a resource and reserve of rare earth elements (REE) in the future. The stages of this research were sample preparation and testing of grain size distribution using the wet and dry sieving method. Grain morphology was observed under a microscope and the determination of mineralogical content with XRD, oxide content with XRF and elemental content with ICP-MS. Fly ash grain size distribution of 76.15% passed 200 mesh sieve (0.074 mm) while the bottom ash was only 0.2%. Grain morphology is sub-rounded and there are still coal that has not been completely burned. The dominant mineral content is quartz, mica mineral (muscovite), clay mineral (kaolinite), lime, siderite, magnetite and hematite. The dominant oxides are SiO2, Al2 O3, Fe2 O3 and CaO. Based on ICP-MS test results, 16 elements of REE were detected. The total REE contents for each sample, FA and BA were 264.97 ppm and 49.22 ppm, respectively. REE of CCP from Banjarsari power plant which has the potential to be extracted is the content of cerium 80.5 ppm, neodymium 42.9 ppm, yttrium 41.8 ppm and lanthanum 31.4 ppm from fly ash while at the bottom ash there is no potential to be extracted.